Family study of Haemoglobin Arya in a Malaysian family - Nahanthiran, Subithira; Nik Mustapha, Nik Hafidzah; Mohd Yasin, Norafiza; Idris, Faridah; Md Noor, Sabariah (Malaysian Society of Pathologists, 2024)
Thalassemia and haemoglobinopathies are relatively common among Malaysians. One of the rare haemoglobinopathies reported is Haemoglobin (Hb) Arya, which occurs due to substitution of aspartic acid at residue 47 of the alpha chain by asparagine. Here, we report the detection of Hb Arya in a Malaysian family, which was detected incidentally during family screening. Case Report: A 16 years-old girl, clinically asymptomatic was noted to have low mean corpuscular haemoglobin (MCV) with normal Hb level. Hb analysis using capillary electrophoresis (CE) showed reduced Hb A of 76.5%, Hb A2 of 1.6% with presence of small peak at Zone 1 likely A2’. There was also a small peak noted at Hb D zone and Hb S zones which quantified as 1.5% and 20% respectively. Supplementary test by high performance liquid chromatography (HPLC) showed a prominent peak at D-window (19.6%) and a small peak at S-window (0.6%). DNA analysis revealed a heterozygous state of α2 codon 47 Hb Arya mutation. Subsequent family study showed a similar mutation in the father and sister of the index case. Conclusion: Very few reports are available up to date regarding Hb Arya. This report highlights the rare haemoglobinopathy in a Malay family in Malaysia that contributes to the growing literature of this rare haemoglobin variant.